A recycled waste polyurethane composite modified concrete and a preparation method thereof

CN122878091APending Publication Date: 2026-10-09BEIJING SHENGRUIJIA NEW MATERIAL TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611164069.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

该专利技术主要利用聚氨酯乳液进行发泡提升材料的力学性能,对于如何实现废旧聚氨酯的再生利用缺乏研究,同时混凝土材料的力学强度也有进一步提升的空间

Benefits of technology

(1)本发明的再生聚氨酯以废旧聚氨酯醇解的再生聚醚多元醇和甲苯二异氰酸酯作为原料,并引入天然长链多元醇蓖麻油和羟基硅油,蓖麻油的侧链柔性烷基链能够提升材料韧性,减少混凝土内部应力集中产生的微裂纹,羟基硅油则将有机硅链段接枝至聚氨酯分子骨架提升与纤维材料的浸润性,并通过Si-O-Si键的高键能缓冲荷载应力,从而保证混凝土材料具有良好的力学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878091A_ABST
    Figure CN122878091A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of light building materials, and particularly relates to a recycled waste polyurethane composite modified concrete and a preparation method. The preparation method of the recycled waste polyurethane composite modified concrete comprises the following steps: S1, first, waste polyurethane is pretreated to obtain waste polyurethane particles, then recycled polyether polyol is prepared by taking the waste polyurethane particles as raw materials, and finally recycled polyurethane is obtained by mixing the recycled polyether polyol, castor oil, toluene diisocyanate and hydroxyl silicone oil and performing a polymerization reaction; S2, first, the recycled polyurethane and aggregates are uniformly mixed, then cement, fly ash, fiber material, defoaming agent, water reducing agent and deionized water are added and stirred and mixed, and then the mixture is formed by casting and maintained to form the recycled waste polyurethane composite modified concrete. The application not only ensures good compressive strength and tensile strength of the concrete material, but also realizes the recycling of waste polyurethane, so that the waste polyurethane can be better applied in the field of light building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lightweight building materials technology, specifically relating to a recycled waste polyurethane composite modified concrete and its preparation method. Background Technology

[0002] Concrete is the most widely used and consumed artificial stone in modern construction engineering. It is made by mixing cement, sand, water, admixtures, and mineral admixtures in appropriate proportions, followed by pouring, curing, and hardening. By controlling the hydration reaction mechanism of the cement matrix, the theory of aggregate gradation (continuous gradation curve optimization), and the synergistic effect of chemical admixtures, concrete can achieve a precise match between workability and durability of hardened concrete. Therefore, it demonstrates its irreplaceable role in technologies such as super high-rise buildings, cross-sea bridges, and nuclear power plant shielding structures. However, traditional concrete suffers from many problems such as cracking, pitting, and frost heave, leading to increased curing costs and reduced durability.

[0003] Polyurethane concrete is a modified concrete formed by mixing polyurethane binder as the matrix material with aggregates of a certain gradation. Due to its good interlayer bonding force, excellent high-temperature stability, good low-temperature crack resistance, and convenient and easy-to-control construction process, polyurethane concrete is widely used in steel bridge deck paving, rapid repair of bridge expansion joints, and emergency repair of highways and airport runways. The main advantages of polyurethane concrete include: (1) significant lightweight and shock-absorbing characteristics. The addition of polyurethane increases the porosity and reduces the density of the concrete, which greatly reduces the overall load of the building as a lightweight building material; (2) good interfacial adhesion. Polyurethane has good interfacial adhesion with SBS modified asphalt, limestone, etc., thus ensuring the integrity of the structure; (3) excellent thermal insulation performance. Polyurethane itself has a very low thermal conductivity. When applied to concrete, it can significantly reduce the thermal conductivity of the material.

[0004] Chinese patent (publication number CN120423834A) discloses a high-strength, high-toughness polyurethane concrete, comprising the following components by weight: 400-800 parts ordinary silicate cement, 15-20 parts toughening hybrid fiber, 6-50 parts polyurethane emulsion, 2-5 parts foaming agent, 0.02-0.04 parts foam stabilizer, 180-300 parts water, 10-30 parts dry sand, 1-5 parts lime powder, 1-2 parts microcrystalline cellulose, 2-4 parts water glass, 8-10 parts modified rubber powder, and 10-15 parts carbon fiber powder. This invention uses a physical foaming method, resulting in a more uniform pore structure after hardening. This patented technology primarily utilizes polyurethane emulsion for foaming to improve the mechanical properties of the material. However, it lacks research on how to recycle waste polyurethane, and there is room for further improvement in the mechanical strength of the concrete material.

[0005] Therefore, there is an urgent need for a composite modified concrete that can recycle waste polyurethane and work together with other functional components to ensure good compressive and tensile strength of the material while realizing the recycling of waste polyurethane, so as to better promote its application in the field of lightweight building materials. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the present invention aims to provide a recycled waste polyurethane composite modified concrete and its preparation method. The invention first pre-treats waste polyurethane to obtain waste polyurethane particles. Then, recycled polyether polyol is prepared using the waste polyurethane particles as raw material. The recycled polyether polyol is then mixed with castor oil, toluene diisocyanate, and hydroxyl silicone oil for polymerization to obtain recycled polyurethane. Next, the recycled polyurethane is mixed with aggregates, and cement, fly ash, fiber materials, defoamer, water-reducing agent, and deionized water are added and stirred. The mixture is then cast into molds and cured to obtain the recycled waste polyurethane composite modified concrete. This invention recycles waste polyurethane and works synergistically with other functional components to ensure the material has good mechanical strength.

[0007] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: In a first aspect, this invention provides a method for preparing recycled waste polyurethane composite modified concrete, comprising the following steps: S1. First, waste polyurethane is pretreated to obtain waste polyurethane particles. Then, the waste polyurethane particles are used as raw materials to prepare recycled polyether polyol. Finally, the recycled polyether polyol is mixed with castor oil, toluene diisocyanate and hydroxyl silicone oil to carry out a polymerization reaction to obtain recycled polyurethane. S2. First, mix the recycled polyurethane and aggregates mentioned in step S1. Then, add cement, fly ash, fiber materials, defoamer, water-reducing agent, and deionized water and stir to mix. Cast the mixture into a mold and cure it to obtain recycled waste polyurethane composite modified concrete.

[0008] As a preferred embodiment of the present invention, the curing and shaping time in step S2 is 7 days.

[0009] As a preferred technical solution of the present invention, the components in step S2 include, by weight: 280-300 parts cement, 900-1000 parts aggregate, 20-30 parts recycled polyurethane, 10-20 parts fly ash, 10-20 parts fiber material, 1.2-1.4 parts defoamer, 2-4 parts water-reducing agent, and 120-130 parts deionized water.

[0010] As a preferred embodiment of the present invention, the weight parts of the recycled polyurethane may be 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, or 30 parts, etc.

[0011] As a preferred embodiment of the present invention, the weight parts of the fly ash may be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, or 20 parts, etc.

[0012] As a preferred embodiment of the present invention, the weight parts of the fiber material may be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, or 20 parts, etc.

[0013] As a preferred embodiment of the present invention, the water-reducing agent may be present in 2, 3, or 4 parts by weight, etc.

[0014] As a preferred technical solution of the present invention, the pretreatment step is as follows: after cleaning and drying the waste polyurethane, it is transferred to a shear crusher for crushing and passing it through an 80-mesh sieve to obtain waste polyurethane particles.

[0015] As a preferred technical solution of the present invention, the preparation steps of the recycled polyether polyol are as follows: by weight, 90-100 parts of ethylene glycol and 100-110 parts of ethanolamine are mixed in a reaction vessel, then 1.4-1.8 parts of potassium hydroxide are added and the temperature is raised to 110-120°C and stirred for 20-30 minutes. Then 180-200 parts of the waste polyurethane particles are added and stirred and reacted at 160-165°C for 4-6 hours. After the reaction is completed, the mixture is rotary evaporated, washed with water, and dried to obtain the recycled polyether polyol.

[0016] As a preferred embodiment of the present invention, the polymerization reaction steps are as follows: 10-20 parts by weight of recycled polyether polyol, 10-20 parts by weight of castor oil and 80-90 parts by weight of cyclohexanone are added to a reaction vessel, stirred at 200-300 r / min and 15-30 parts by weight of toluene diisocyanate are added, the temperature is raised to 65-70°C and reacted for 120-140 min, then 10-20 parts by weight of hydroxyl silicone oil, 0.4-0.6 parts by weight of 1,4-butanediol, 0.1-0.2 parts by weight of dibutyltin dilaurate and 0.2-0.4 parts by weight of trimethylolpropane are added, and the reaction is carried out at 75-80°C for 150-200 min. After the reaction is completed, the mixture is rotary evaporated to obtain recycled polyurethane.

[0017] This invention first cleans, dries, crushes, and sieves waste polyurethane to obtain waste polyurethane particles. Then, using ethylene glycol and ethanolamine as a degradation agent and potassium hydroxide as a catalyst, the waste polyurethane is alcoholyzed to form recycled polyether polyol. Finally, using the recycled polyether polyol, castor oil, toluene diisocyanate, and hydroxyl silicone oil as raw materials, 1,4-butanediol as a small molecule chain extender, and trimethylolpropane as a crosslinking agent, recycled polyurethane is prepared through a polymerization reaction.

[0018] As a preferred embodiment of the present invention, the fly ash is surface-modified fly ash.

[0019] As a preferred technical solution of the present invention, the preparation method of the surface-modified fly ash is as follows: first, fly ash particles are mixed with magnesium chloride and sodium hydroxide and stirred to obtain magnesium-doped fly ash; then, dopamine hydrochloride is used to modify the magnesium-doped fly ash to obtain surface-modified fly ash.

[0020] As a preferred technical solution of the present invention, the preparation steps of the magnesium-doped fly ash are as follows: by weight, 10-20 parts of fly ash particles are dispersed in 80-100 parts of deionized water, then 8-10 parts of magnesium chloride and 180-200 parts of 1mol / L sodium hydroxide solution are added, the temperature is raised to 85-95℃ and the mixture is stirred for 100-120 min, filtered, and dried to obtain magnesium-doped fly ash.

[0021] As a preferred technical solution of the present invention, the modification treatment steps are as follows: by weight, 10-20 parts of dopamine hydrochloride are added to 800-900 parts of deionized water and stirred to dissolve, then 4-6 parts of tris(hydroxymethyl)aminomethane and 10-20 parts of magnesium-doped fly ash are added, stirred at 30-40°C for 40-48 hours, centrifuged, washed with water, and vacuum dried to obtain surface-modified fly ash.

[0022] This invention first uses fly ash particles as the main raw material, and achieves uniform doping of magnesium element by stirring and reacting with magnesium chloride and sodium hydroxide, thereby obtaining magnesium-doped fly ash; then, the magnesium-doped fly ash is added to a dopamine hydrochloride solution, and under the action of tris(hydroxymethyl)aminomethane, dopamine hydrochloride undergoes oxidative self-polymerization after deprotonation, generating a polydopamine modification layer rich in catechol and amino groups on the surface of the fly ash particles in situ, and finally obtaining dopamine-modified magnesium-doped fly ash.

[0023] As a preferred embodiment of the present invention, the fiber material is glass fiber and polypropylene fiber.

[0024] As a preferred embodiment of the present invention, the mass ratio of glass fiber to polypropylene fiber is (1~3):1.

[0025] As a preferred embodiment of the present invention, the glass fiber is silane-treated chopped glass fiber, wherein the fiber diameter of the silane-treated chopped glass fiber is 5~15μm and the short fiber length is 2~5mm.

[0026] As a preferred embodiment of the present invention, the polypropylene fiber is a Y-shaped cross-section polypropylene mesh fiber, the fiber length of the Y-shaped cross-section polypropylene mesh fiber is 10~20mm, the tensile strength is ≥350MPa, the elongation at break is 15~20%, and the elastic modulus is ≥3500MPa.

[0027] The fiber material of this invention is a blend of silane-treated glass chopped fibers and Y-shaped cross-section polypropylene mesh fibers. By controlling the mass ratio of the two, a good synergistic effect is achieved, thereby improving the overall performance of recycled waste polyurethane composite modified concrete.

[0028] As a preferred embodiment of the present invention, the aggregate is river sand or quartz sand.

[0029] As a preferred embodiment of the present invention, the water-reducing agent is a polycarboxylate-based water-reducing agent or a naphthalene-based water-reducing agent.

[0030] A second aspect of the present invention provides a recycled waste polyurethane composite modified concrete prepared by the preparation method described in the first aspect.

[0031] Compared with the prior art, the beneficial effects of the present invention are: (1) The recycled polyurethane of the present invention uses recycled polyether polyol and toluene diisocyanate from the alcoholysis of waste polyurethane as raw materials, and introduces natural long-chain polyol castor oil and hydroxyl silicone oil. The flexible alkyl chain of castor oil can improve the toughness of the material and reduce the microcracks caused by stress concentration inside the concrete. The hydroxyl silicone oil grafts organosilicon segments to the polyurethane molecular skeleton to improve the wettability with fiber materials, and buffers the load stress through the high bond energy of Si-O-Si bond, thereby ensuring that the concrete material has good mechanical properties.

[0032] (2) The surface-modified fly ash of the present invention forms an active magnesium compound through the doping of magnesium element, which helps the concrete system to continuously generate composite gel during the hydration process. The dopamine modification layer can form chemical bond connection at the multiphase interface to greatly improve the interfacial shear strength, thereby making the load uniformly transferred to avoid stress concentration, eliminating weak joints at the interface, and thus achieving the goal of improving compressive strength and tensile strength.

[0033] (3) In the composite fiber material of the present invention, the silane-treated glass short fiber can greatly improve the interfacial bonding between the fiber and the cement matrix, thereby more effectively transferring and bearing the load. The Y-shaped cross-section polypropylene mesh fiber has a high specific surface area and excellent dispersion performance, forming a strong three-dimensional mesh support inside the concrete. It can improve the rigidity and ultimate strength of the matrix through the former, and can also seal micron-level original microcracks and delay crack initiation with the latter. The two are used together to form gradient toughening, thereby improving the mechanical strength of the concrete. Attached Figure Description

[0034] Figure 1 The images show the FTIR spectra of recycled polyurethane and waste polyurethane in Example 1. Detailed Implementation

[0035] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.

[0036] The sources of some components in the examples and comparative examples are as follows: The waste polyurethane originated from Suzhou Suxie Scrap Automobile Recycling and Dismantling Co., Ltd. Ethylene glycol, CAS No. 107-21-1, was purchased from Sinopharm Chemical Reagent Co., Ltd. Ethanolamine, CAS No. 141-43-5, was purchased from Sinopharm Chemical Reagent Co., Ltd. Potassium hydroxide, CAS No. 1310-58-3, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Castor oil, CAS No. 8001-79-4, purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Toluene diisocyanate, product number T135411, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Hydroxyl silicone oil, brand name Siwn-OH203B, purchased from Nanjing Silicon Innovation Materials Co., Ltd. 1,4-Butanediol, CAS No. 110-63-4, purchased from Sinopharm Chemical Reagent Co., Ltd. Trimethylolpropane, CAS No. 77-99-6, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Fly ash granules, product number A01085, were purchased from Wuhan Jiyesheng Chemical Co., Ltd. Magnesium chloride, CAS No. 7786-30-3, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Dopamine hydrochloride, CAS No. 62-31-7, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Tris(hydroxymethyl)aminomethane, CAS No. 77-86-1, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Silane-treated chopped glass fibers, grade T436H, with a fiber diameter of 11μm and a short fiber length of 3mm, were purchased from Taishan Glass Fiber Co., Ltd. Ordinary glass chopped fiber, model 568H, purchased from China Jushi Group Co., Ltd. Y-shaped cross-section polypropylene mesh fiber, fiber length 10mm, tensile strength 360MPa, elongation at break 18%; Ordinary polypropylene short fiber, model HY-430, purchased from Shandong Hongyao Copper Co., Ltd. Sulfoaluminate cement, purchased from Hubei Yicheng Anda Special Cement Co., Ltd. Defoamer, model BYK-054 T, purchased from BYK Chemicals; Polycarboxylate superplasticizer, model JF-HP, purchased from Shandong Liangzheng New Material Technology Co., Ltd. Naphthalene-based water-reducing agent, model JF-Ⅰ, purchased from Shandong Liangzheng New Material Technology Co., Ltd. Example

[0037] This embodiment provides a method for preparing recycled waste polyurethane composite modified concrete, including the following steps: S1. After cleaning and drying the waste polyurethane, transfer it to a shear mill for crushing and pass it through an 80-mesh sieve to obtain waste polyurethane particles. By weight, mix 100 parts of ethylene glycol and 110 parts of ethanolamine in a reactor, then add 1.8 parts of potassium hydroxide and heat to 120°C and stir for 30 min. Then add 200 parts of the waste polyurethane particles and stir and react at 165°C for 4 h. After the reaction is completed, rotary evaporate, wash with water, and dry to obtain recycled polyether polyol. Add 20 parts of recycled polyether polyol, 20 parts of castor oil, and 90 parts of cyclohexanone to a reactor, stir at 300 r / min, and add 30 parts of toluene diisocyanate. Heat to 70°C and react for 120 min. Then add 20 parts of hydroxyl silicone oil, 0.6 parts of 1,4-butanediol, 0.2 parts of dibutyltin dilaurate, and 0.4 parts of trimethylolpropane. React at 80°C for 150 min. After the reaction is completed, rotary evaporate to obtain recycled polyurethane. FTIR plots of recycled polyurethane and waste polyurethane are shown below. Figure 1 As shown.

[0038] S2. First, mix the 30 parts of recycled polyurethane and 1000 parts of river sand mentioned in step S1. Then, add 300 parts of sulfoaluminate cement, 20 parts of surface-modified fly ash, 20 parts of fiber material (15 parts of silane-treated glass chopped fiber and 5 parts of Y-shaped cross-section polypropylene mesh fiber), 1.4 parts of defoamer, 4 parts of polycarboxylate superplasticizer, and 130 parts of deionized water. Stir and mix, then cast into a mold and cure for 7 days to obtain recycled waste polyurethane composite modified concrete.

[0039] Preparation of the surface-modified fly ash: By weight, 20 parts of fly ash particles were dispersed in 100 parts of deionized water, then 10 parts of magnesium chloride and 200 parts of 1 mol / L sodium hydroxide solution were added, the mixture was heated to 95℃ and stirred for 100 min, filtered, and dried to obtain magnesium-doped fly ash; 20 parts of dopamine hydrochloride were added to 900 parts of deionized water and stirred to dissolve, then 6 parts of tris(hydroxymethyl)aminomethane and 20 parts of magnesium-doped fly ash were added, the mixture was stirred at 40℃ for 40 h, centrifuged, washed with water, and vacuum dried to obtain surface-modified fly ash. Example

[0040] This embodiment provides a method for preparing recycled waste polyurethane composite modified concrete, including the following steps: S1. After cleaning and drying the waste polyurethane, transfer it to a shear mill for crushing and pass it through an 80-mesh sieve to obtain waste polyurethane particles. By weight, mix 90 parts of ethylene glycol and 100 parts of ethanolamine in a reactor, then add 1.4 parts of potassium hydroxide and heat to 110°C and stir for 30 min. Then add 180 parts of the waste polyurethane particles and stir and react at 160°C for 6 h. After the reaction is complete, rotary evaporate, wash with water, and dry to obtain recycled polyether polyol. Add 10 parts of recycled polyether polyol, 10 parts of castor oil, and 80 parts of cyclohexanone to a reactor, stir at 200 r / min, and add 15 parts of toluene diisocyanate. Heat to 65°C and react for 140 min. Then add 10 parts of hydroxyl silicone oil, 0.4 parts of 1,4-butanediol, 0.1 parts of dibutyltin dilaurate, and 0.2 parts of trimethylolpropane. React at 75°C for 200 min. After the reaction is complete, rotary evaporate to obtain recycled polyurethane.

[0041] S2. First, mix 20 parts of recycled polyurethane and 900 parts of quartz sand mentioned in step S1. Then, add 280 parts of sulfoaluminate cement, 10 parts of surface-modified fly ash, 10 parts of fiber material (5 parts of silane-treated glass chopped fiber and 5 parts of Y-shaped cross-section polypropylene mesh fiber), 1.2 parts of defoamer, 2 parts of naphthalene-based water-reducing agent, and 120 parts of deionized water. Stir and mix, then cast into a mold and cure for 7 days to obtain recycled waste polyurethane composite modified concrete.

[0042] Preparation of the surface-modified fly ash: By weight, 10 parts of fly ash particles were dispersed in 80 parts of deionized water, then 8 parts of magnesium chloride and 180 parts of 1 mol / L sodium hydroxide solution were added, the mixture was heated to 85℃ and stirred for 120 min, filtered, and dried to obtain magnesium-doped fly ash; 10 parts of dopamine hydrochloride were added to 800 parts of deionized water and stirred to dissolve, then 4 parts of tris(hydroxymethyl)aminomethane and 10 parts of magnesium-doped fly ash were added, the mixture was stirred at 30℃ for 48 h, centrifuged, washed with water, and vacuum dried to obtain surface-modified fly ash. Example

[0043] This embodiment provides a method for preparing recycled waste polyurethane composite modified concrete, including the following steps: S1. After cleaning and drying the waste polyurethane, transfer it to a shear mill for crushing and pass it through an 80-mesh sieve to obtain waste polyurethane particles. By weight, mix 96 parts of ethylene glycol and 104 parts of ethanolamine in a reactor, then add 1.6 parts of potassium hydroxide and heat to 115°C and stir for 28 min. Then add 190 parts of the waste polyurethane particles and stir and react at 162°C for 5 h. After the reaction is complete, rotary evaporate, wash with water, and dry to obtain recycled polyether polyol. Add 16 parts of recycled polyether polyol, 14 parts of castor oil, and 85 parts of cyclohexanone to a reactor, stir at 250 r / min, and add 19 parts of toluene diisocyanate. Heat to 68°C and react for 130 min. Then add 16 parts of hydroxyl silicone oil, 0.5 parts of 1,4-butanediol, 0.15 parts of dibutyltin dilaurate, and 0.3 parts of trimethylolpropane. React at 78°C for 180 min. After the reaction is complete, rotary evaporate to obtain recycled polyurethane.

[0044] S2. First, mix 25 parts of recycled polyurethane and 950 parts of river sand mentioned in step S1. Then, add 286 parts of sulfoaluminate cement, 16 parts of surface-modified fly ash, 15 parts of fiber material (10 parts of silane-treated glass chopped fiber and 5 parts of Y-shaped cross-section polypropylene mesh fiber), 1.3 parts of defoamer, 3 parts of polycarboxylate superplasticizer, and 125 parts of deionized water. Stir and mix, then mold and cure for 7 days to obtain recycled waste polyurethane composite modified concrete.

[0045] Preparation of the surface-modified fly ash: By weight, 16 parts of fly ash particles were dispersed in 90 parts of deionized water, then 9 parts of magnesium chloride and 190 parts of 1 mol / L sodium hydroxide solution were added, the mixture was heated to 88℃ and stirred for 110 min, filtered, and dried to obtain magnesium-doped fly ash; 16 parts of dopamine hydrochloride were added to 870 parts of deionized water and stirred to dissolve, then 5 parts of tris(hydroxymethyl)aminomethane and 16 parts of magnesium-doped fly ash were added, the mixture was stirred at 35℃ for 44 h, centrifuged, washed with water, and vacuum dried to obtain surface-modified fly ash.

[0046] Comparative Example 1 The difference between this comparative example and Example 1 is that waste polyurethane particles are used instead of recycled polyurethane.

[0047] Comparative Example 2 The difference between this comparative example and Example 1 is that fly ash particles (item number A01085) are used instead of surface-modified fly ash.

[0048] Comparative Example 3 The difference between this comparative example and Example 1 is that the fiber material was changed to 15 parts of ordinary glass chopped fiber (model 568H) and 5 parts of Y-shaped cross-section polypropylene mesh fiber.

[0049] Comparative Example 4 The difference between this comparative example and Example 1 is that the fiber material was changed to 15 parts of silane-treated glass chopped fiber and 5 parts of ordinary polypropylene short fiber (model HY-430).

[0050] Comparative Example 5 The difference between this comparative example and Example 1 is that the fiber material was changed to 20 parts of silane-treated chopped glass fibers.

[0051] Comparative Example 6 The difference between this comparative example and Example 1 is that the fiber material is changed to 20 parts of Y-shaped cross-section polypropylene mesh fiber.

[0052] Performance testing The water absorption, compressive strength, and tensile strength of the above-mentioned examples and comparative examples were tested in accordance with the requirements of GB / T 50081-2019 Standard for Test Methods of Physical and Mechanical Properties of Concrete.

[0053] The performance test data above are shown in Table 1.

[0054] Table 1 Performance Test Results Example 1 5.1 68.6 8.8 Example 2 5.4 67.9 8.3 Example 3 5.2 68.3 8.5 Comparative Example 1 5.9 55.4 4.9 Comparative Example 2 5.7 56.8 5.2 Comparative Example 3 5.5 60.9 7.1 Comparative Example 4 5.8 61.5 7.3 Comparative Example 5 5.6 60.4 6.8 Comparative Example 6 5.9 59.7 6.4 As can be seen from the above, the present invention first pre-treats waste polyurethane to obtain waste polyurethane particles, then uses the waste polyurethane particles as raw materials to prepare recycled polyether polyol, and then mixes the recycled polyether polyol with castor oil, toluene diisocyanate and hydroxyl silicone oil to carry out a polymerization reaction to obtain recycled polyurethane. Next, the recycled polyurethane and aggregate are mixed evenly, and cement, fly ash, fiber materials, defoamer, water-reducing agent and deionized water are added and stirred. The mixture is then cast into molds and cured to obtain recycled waste polyurethane composite modified concrete (Examples 1 to 3), which has better comprehensive performance.

[0055] Compared to Example 1, the use of waste polyurethane particles instead of recycled polyurethane lacks the effect of castor oil flexible alkyl chains and organosilicon segments, resulting in a decrease in the mechanical strength of the concrete (Comparative Example 1); compared to Example 1, the use of fly ash particles (item number A01085) instead of surface-modified fly ash lacks the effect of surface-modified fly ash, resulting in a decrease in the mechanical strength of the concrete (Comparative Example 2); compared to Example 1, the fiber material was changed to 15 parts of ordinary glass chopped fibers (model 568H) and 5 parts of Y-section polypropylene mesh fibers, lacking the effect of silane-treated glass chopped fibers, resulting in a decrease in the mechanical strength of the concrete (Comparative Example 3); compared to Example 1... Comparative Example 4: When the fiber material was changed to 15 parts silane-treated chopped glass fibers and 5 parts ordinary polypropylene short fibers (model HY-430), the lack of Y-shaped cross-section polypropylene mesh fibers resulted in a decrease in the mechanical strength of the concrete (Comparative Example 5). When the fiber material was changed to 20 parts silane-treated chopped glass fibers, the lack of Y-shaped cross-section polypropylene mesh fibers resulted in a poor effect, resulting in a decrease in the mechanical strength of the concrete (Comparative Example 6).

Claims

1. A method for preparing recycled waste polyurethane composite modified concrete, characterized in that, Includes the following steps: S1. First, waste polyurethane is pretreated to obtain waste polyurethane particles. Then, the waste polyurethane particles are used as raw materials to prepare recycled polyether polyol. Finally, the recycled polyether polyol is mixed with castor oil, toluene diisocyanate and hydroxyl silicone oil to carry out a polymerization reaction to obtain recycled polyurethane. S2. First, mix the recycled polyurethane and aggregates mentioned in step S1. Then, add cement, fly ash, fiber materials, defoamer, water-reducing agent, and deionized water and stir to mix. Cast the mixture into a mold and cure it to obtain recycled waste polyurethane composite modified concrete.

2. The method for preparing recycled waste polyurethane composite modified concrete according to claim 1, characterized in that, The components in step S2, by weight, include: 280-300 parts cement, 900-1000 parts aggregate, 20-30 parts recycled polyurethane, 10-20 parts fly ash, 10-20 parts fiber material, 1.2-1.4 parts defoamer, 2-4 parts water-reducing agent, and 120-130 parts deionized water.

3. The method for preparing recycled waste polyurethane composite modified concrete according to claim 1, characterized in that, The preparation steps of the recycled polyether polyol are as follows: by weight, 90-100 parts of ethylene glycol and 100-110 parts of ethanolamine are mixed in a reactor, then 1.4-1.8 parts of potassium hydroxide are added and the mixture is heated to 110-120°C and stirred for 20-30 minutes. Then, 180-200 parts of the waste polyurethane particles are added and the mixture is stirred and reacted at 160-165°C for 4-6 hours. After the reaction is completed, the mixture is rotary evaporated, washed with water, and dried to obtain the recycled polyether polyol.

4. The method for preparing recycled waste polyurethane composite modified concrete according to claim 1, characterized in that, The polymerization reaction steps are as follows: 10-20 parts by weight of recycled polyether polyol, 10-20 parts by weight of castor oil and 80-90 parts by weight of cyclohexanone are added to a reactor. The mixture is stirred at 200-300 r / min and 15-30 parts by weight of toluene diisocyanate are added. The temperature is raised to 65-70℃ and the reaction is carried out for 120-140 min. Then, 10-20 parts by weight of hydroxyl silicone oil, 0.4-0.6 parts by weight of 1,4-butanediol, 0.1-0.2 parts by weight of dibutyltin dilaurate and 0.2-0.4 parts by weight of trimethylolpropane are added. The reaction is carried out at 75-80℃ for 150-200 min. After the reaction is completed, the mixture is rotary evaporated to obtain recycled polyurethane.

5. The method for preparing recycled waste polyurethane composite modified concrete according to claim 1, characterized in that, The fly ash is surface-modified fly ash; The preparation method of the surface-modified fly ash is as follows: first, fly ash particles are mixed with magnesium chloride and sodium hydroxide and stirred to obtain magnesium-doped fly ash; then, dopamine hydrochloride is used to modify the magnesium-doped fly ash to obtain surface-modified fly ash.

6. The method for preparing recycled waste polyurethane composite modified concrete according to claim 5, characterized in that, The preparation steps of the magnesium-doped fly ash are as follows: by weight, 10-20 parts of fly ash particles are dispersed in 80-100 parts of deionized water, then 8-10 parts of magnesium chloride and 180-200 parts of 1mol / L sodium hydroxide solution are added, the temperature is raised to 85-95℃ and the mixture is stirred for 100-120 min, filtered and dried to obtain magnesium-doped fly ash.

7. The method for preparing recycled waste polyurethane composite modified concrete according to claim 5, characterized in that, The modification process is as follows: by weight, 10-20 parts of dopamine hydrochloride are added to 800-900 parts of deionized water and stirred to dissolve. Then, 4-6 parts of tris(hydroxymethyl)aminomethane and 10-20 parts of magnesium-doped fly ash are added. The mixture is stirred at 30-40°C for 40-48 hours, centrifuged, washed with water, and vacuum dried to obtain surface-modified fly ash.

8. The method for preparing recycled waste polyurethane composite modified concrete according to claim 1, characterized in that, The fiber material is glass fiber and polypropylene fiber; The mass ratio of glass fiber to polypropylene fiber is (1~3):

1.

9. The method for preparing recycled waste polyurethane composite modified concrete according to claim 8, characterized in that, The glass fiber is silane-treated chopped glass fiber, and the fiber diameter of the silane-treated chopped glass fiber is 5~15μm, and the short fiber length is 2~5mm; The polypropylene fiber is a Y-shaped cross-section polypropylene mesh fiber with a fiber length of 10~20mm, a breaking strength ≥350MPa, a breaking elongation of 15~20%, and an elastic modulus ≥3500MPa.

10. A type of recycled waste polyurethane composite modified concrete, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-strength and high-toughness polyurethane concrete as well as preparation method and application thereof

    CN120423834A